Analisis Implementasi Permendikbud Nomor 111 Tahun 2014 Tentang Bimbingan Dan Konseling - Rifqi Muhammad (FAKULTAS TARBIYAH IAI SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2021)
This paper aims to analyze Permendikbud No. 111 of 2014 concerning Guidance and Counseling in Primary and Secondary Education. The following is an explanation of the results of the analysis: 1) Permendikbud No. 111/2014 wants the Basic Education and Secondary Education patterns to be a single pattern that is implemented nationally. So that there is no more dualistic patterns in the implementation of BK; 2) The mistake of saying that BK teachers are professional educators; 3) Permendikbud No. 111/2014 do not speak SKAKK, so far BK teachers are still using SKAKK and SKAKG, in the future they must have the courage to determine Academic Qualification Standards and Competency of BK teachers; 4) The terms counselee, counseling teacher, and counselor are correct. There is a new term, namely